2016
DOI: 10.1111/ajfs.12123
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Currency Debt Financing, Firm Value, and Risk: Evidence from Korea Surrounding the Global Financial Crisis

Abstract: We examine the valuation effect of foreign currency (FC) debt financing, relative to local currency (LC) debt financing. Employing extensive data from Korean firms during 2002–2012, we document strong evidence that firms using FC debt financing have significantly lower values than firms using LC debt financing. Even during the pre‐global financial crisis period when the LC value appreciated, we find no evidence of a higher firm value associated with FC debt financing. Further analyses on the possible causes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The negative effect of foreign currency debt on firm value reaffirms Korean firms' exposures to increased financing risk and capital costs through the serious liquidity and currency mismatches that the record‐level of foreign currency debt brought during the crisis, deteriorating Korean firms' business performance. This finding is consistent with the evidence in previous studies (e.g., Allayannis et al, 2003; Bae et al, 2016).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The negative effect of foreign currency debt on firm value reaffirms Korean firms' exposures to increased financing risk and capital costs through the serious liquidity and currency mismatches that the record‐level of foreign currency debt brought during the crisis, deteriorating Korean firms' business performance. This finding is consistent with the evidence in previous studies (e.g., Allayannis et al, 2003; Bae et al, 2016).…”
Section: Resultssupporting
confidence: 94%
“…Financing risk wise, foreign currency debt ratio of Korean firms reached a record level of 6.4% during the global financial crisis, which was a significant increase from its precrisis level of 6.1% and a level well above their foreign currency assets ratio of 5.3% (Bae et al, 2016). Accordingly, Korean firms were exposed to increased financing risk through a serious liquidity mismatch between foreign currency debt and foreign currency assets, causing their financial positions to worsen.…”
Section: Introductionmentioning
confidence: 99%
“…It is also shown that sample Korean firms incur an average loss of 0.08% of total assets from currency derivatives transactions during our sample period, and that high EXE firms incur significantly larger transaction losses than low EXE firms (0.14% vs. 0.01%). These findings suggest the possibilities of ineffective and complex risk management programs (Copeland & Joshi, ; Hagelin & Pramborg, ), implementation of non‐optimal hedges and excessive costs of currency derivatives use (Bae et al, ); and/or constraints in managing foreign exchange risk (Allayannis et al, ; Clark & Judge, ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, firms often fail to employ optimal hedge ratios or proper transactions of currency derivatives for hedging, thus, either over‐ or under‐hedging their exchange rate exposures. Then, the consequence would be such that as currency derivatives use may reduce foreign exchange risk, this reduction in risk may not necessarily lead to an increase in firm value due to the non‐optimal hedging and/or excessive costs of hedging (Bae et al, ). To this end, our paper takes empirical approaches distinctively different from those in the existing studies.…”
Section: Literature Review and Main Research Issuesmentioning
confidence: 99%
See 1 more Smart Citation